Review of Treatment for Adenosine Deaminase Deficiency (ADA) Severe Combined Immunodeficiency (SCID) - Secord E; Hartog NL (Therapeutics and Clinical Risk Management, 2022)
Elizabeth Secord,1 Nicholas L Hartog2 1Pediatrics, Division of Allergy and Immunology, Wayne State University School of Medicine, Detroit, MI, USA; 2Pediatrics, Division of Allergy and Immunology, Michigan State University College of Human Medicine, Helen DeVos Children’s Hospital, Grand Rapids, MI, USACorrespondence: Elizabeth Secord, Wayne State University School of Medicine, Wayne Pediatrics, 400 Mack Avenue, Detroit, MI, 48201, USA, Tel +1-313-448-9600, Fax +1-313-448-9978, Email esecord@med.wayne.eduAbstract: Adenosine deaminase deficiency (ADA) is a purine salvage pathway deficiency that results in buildup of toxic metabolites causing death in rapidly dividing cells, especially lymphocytes. The most complete form of ADA leads to severe combined immune deficiency (SCID). Treatment with enzyme replacement therapy (ERT) was developed in the 1970s and became the treatment for ADA SCID by the 1980s. It remains an option for some infants with SCID, and a stopgap measure for others awaiting curative therapy. For some infants with ADA SCID who have matching family donors hematopoietic stem cell transplant (HSCT) is an option for cure. Gene therapy for ADA SCID, approved in some countries and in trials in others, is becoming possible for more infants with this disorder. This review covers the history of ADA SCID, the treatment options to date and particularly the history of the development of gene therapy for ADA SCID and the current state of the risks and benefits of the gene therapy option.Keywords: adenosine deaminase deficiency, ADA, severe combined immunodeficiency, SCID, enzyme replacement therapy, ERT, gene therapy